Implementasi Metode ORESTE dalam Pemilihan Karir Berdasarkan Minat dan Keterampilan - Hana Kamilia; Helmi Fauzi Siregar (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Career selection is a crucial process that influences a person's satisfaction and success in the workplace. Many individuals, especially students, experience difficulty in determining career choices that align with their interests and skills. Therefore, a system is needed to assist in the decision-making process in an objective and measurable manner. This study aims to implement the ORESTE (Organization Rangement and Synthesis of People's Relationships) method in a decision support system for career selection based on interests and skills. The ORESTE method was used because it can rank alternatives based on multiple criteria without requiring overly complex weighting. The criteria used in this study included gender, interests, skills, salary expectations, and occupation. The research process involved data analysis, weighting, normalization, distance score calculation, and ranking to generate the most appropriate career recommendations. The results show that the ORESTE-based decision support system is capable of providing accurate and relevant career recommendations based on user characteristics. This system is also considered to help students understand their potential and facilitate the career decision-making process. Thus, the application of the ORESTE method has proven effective as an objective, systematic, and efficient decision-making tool in determining career choices according to individual interests and skills.